2003
DOI: 10.1038/sj.mp.4001392
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism (5-HTTLPR) in the serotonin transporter promoter gene is associated with DSM-IV depression subtypes in seasonal affective disorder

Abstract: Serotonergic mechanisms are thought to play an important role in the pathogenesis of seasonal affective disorder (SAD). The expression of the serotonin transporter (5-HTT) is regulated in part by an insertion/deletion polymorphism in the serotonin transporter gene promoter region (5-HTTLPR). The 5-HTTLPR short allele (s) has been associated with anxietyrelated personality traits and depression, and one study observed an association between the 5-HTTLPR s-allele and SAD and the trait of seasonality. We genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 28 publications
5
52
0
1
Order By: Relevance
“…In accordance with previous results (Johansson et al, 2003;Willeit et al, 2003), 5-HTTLPR genotype distribution did not differ significantly between patients with SAD and healthy controls (patients: ll: 22; ls: 38; ss: 13; controls: ll: 26; ls: 35; ss: 9; w 2 (2) ¼ 1.121; p ¼ 0.571). An earlier study reported significant seasonal variations in serotonin uptake velocity in 5-HTTLPR ll homozygous subjects only (Greenberg et al, 1999).…”
Section: -Httlpr and 5-htt Functionsupporting
confidence: 92%
“…In accordance with previous results (Johansson et al, 2003;Willeit et al, 2003), 5-HTTLPR genotype distribution did not differ significantly between patients with SAD and healthy controls (patients: ll: 22; ls: 38; ss: 13; controls: ll: 26; ls: 35; ss: 9; w 2 (2) ¼ 1.121; p ¼ 0.571). An earlier study reported significant seasonal variations in serotonin uptake velocity in 5-HTTLPR ll homozygous subjects only (Greenberg et al, 1999).…”
Section: -Httlpr and 5-htt Functionsupporting
confidence: 92%
“…Many but not all studies have suggested an association between the S allele and abnormal mood states/emotional behaviors (Lesch et al, 1996;Mazzanti et al, 1998;Munafo et al, 2003), depressive illness (Willeit et al, 2003), severity of depressive 5HTTLPR*: group allelic effect, F ϭ 4.8, df ϭ 1, 27, p ϭ 0.037; scanner effect, F ϭ 2.3, df ϭ 1, 27, p ϭ 0.1; gender effect, F ϭ 1.4, df ϭ 1, 27, p ϭ 0.3; interaction effects, allele ϫ scanner, F ϭ 0.3, df ϭ 1, 27, p ϭ 0.6; allele ϫ gender, F ϭ 2.5, df ϭ 1, 27, p ϭ 0.1; scanner ϫ gender, F ϭ 0.6, df ϭ 1, 27, p ϭ 0.5; allele ϫ scanner ϫ gender, F ϭ 0.4, df ϭ 1, 27, p ϭ 0.5. 5-HT 1A (Ϫ1018cϾG)**: group allelic effect, F ϭ 0.001, df ϭ 1, 28, p ϭ 0.973; scanner effect, F ϭ 0.16, df ϭ 1, 28, p ϭ 0.9; gender effect, F ϭ 2.1, df ϭ 1, 28, p ϭ 0.2; interaction effects, allele ϫ scanner, F ϭ 1.1, df ϭ 1, 28, p ϭ 0.3; allele ϫ gender, F ϭ 0.6, df ϭ 1, 28, p ϭ 0.4; scanner ϫ gender, F ϭ 1.7, df ϭ 1, 28, p ϭ 0.2.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the case of ASD, few SNPs have been associated with this condition in GWAS; thus, the LD-pruned set only contained 10 ASD variants, one of these significantly correlated with Δphotoperiod ( Table 2). As for SAD, no GWAS has been performed; a variable number tandem repeat (VNTR) in the serotonin transporter gene (SLC6A4) promoter, which affects expression, is the only variant reproducibly associated with SAD and seasonality [30][31][32]. We used data from a recent analysis [33] and obtained a significant correlation between the frequency of the 14-repeat (short) allele, which predisposes to SAD [30][31][32], and Δphotoperiod (τ = 0.331, Kendall's correlation P value = 0.00115).…”
Section: Genetic Adaptation To Photoperiod and Disease Susceptibilitymentioning
confidence: 99%